The Effect of Production Costs and Economies of Scale on Net Profit and Production Capacity of Small and Medium Enterprises Processing Palm Oil in South Sulawesi - Judijanto, Loso; Apriyanto, Apriyanto; Novitasari, Salwa Aulia (Westscience Press, 2025)
This study examines the effect of production costs and scale efficiency on the net profit and production capacity of small and medium-sized palm oil processing businesses in South Sulawesi. Using a quantitative research design, data were collected from 150 respondents and analyzed with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The results show that production costs have a significant negative effect on net profit but do not significantly influence production capacity. Conversely, scale efficiency has a significant positive effect on both net profit and production capacity. Furthermore, production capacity mediates the relationship between scale efficiency and net profit, highlighting its strategic role in enhancing financial performance. These findings emphasize the importance of cost control measures and efficiency improvement strategies for achieving sustainable growth and competitiveness in the palm oil processing sector. The study offers managerial implications for SME owners and policy recommendations to strengthen operational performance in the industry.